034 Impact of Progesterone Supplementation on Pregnancy Rates Following Timed AI or Embryo Transfer in Beef Cattle Consuming Endophyte-Infected Fescue. (1st February 2016) - Mackey, J. C.; Devine, T. L.; Kennedy, P. M.; Tyson, A. M.; Poore, M. H.; Poole, D. H.
Abstract: Most tall fescue ( Festuca arundinacea ) is infected with a fungal endophyte ( Epichloë coenophiala ) that produces ergot alkaloids; hindering reproductive success by decreasing pregnancy rates and suppressing progesterone (P4) concentrations. The objective of this study was to determine if progesterone supplementation following timed AI or embryo transfer (ET) increases pregnancy rates (PR) of cattle consuming endophyte-infected tall fescue. Nulliparous and multiparous cattle were maintained on stockpiled endophyte-infected tall fescue. All cattle were synchronized using the standard 7d CO-Synch +CIDR® program. Cattle were inseminated 60-66 hr post-CIDR removal for TAI. In the ET group, cattle received either a fresh or frozen embryo on day 10 post- CIDR removal. Cattle received either a CIDR blank (control) or active CIDR ten d post-CIDR removal. Pregnancy and embryo area were determined by ultrasonography at d 30 of gestation. Data was analyzed using a PROC GLIMMIX procedure of SAS and examined for effects of treatment, year, location, and age. Statistical significance was determined at P < 0.05 and a tendency at 0.05<P<0.10. There was no difference in PR with supplemental P4 7d following TAI in multiparous cattle (P4-21.08% vs. control-31.6%; P>0.05) or nulliparous cattle (P4-41.7% vs. control-41.7%; P >0.05). However, PR in heifers receiving P4 supplementation tended to differ by location (location1- 43.3% vs. location2 - 71.7%). There was a significant effect of year (P<0.05) for ET groups, therefore yr 1 and 2 were analyzed independently. In yr 1, P4 supplementation increased PR in ET cattle compared to controls (84.6% vs. 60.1%, respectfully; P <0.05). Additionally, supplemental P4 improved PR in cattle >7 yrs old (P4-98.7% vs. control-57.2%; P <0.05) and increased embryo retention in cattle receiving a frozen embryo (P4-96.7% vs. control-59.7%; P <0.05); this was not observed with fresh embryos. In the yr 2, there was no difference in PR with supplemental P4 (P4-36.8% vs controls-34.5%; P >0.05). However, supplemental P4 tended to increase pregnancy rates in Angus cattle receiving embryos (P4-43.8% vs. control-17.6%; P <0.10), but was not observed in crossbred cattle. Additional progesterone did not affect embryo area in either the TAI or ET groups. While progesterone supplementation throughout maternal recognition of pregnancy significantly increased PR in cattle receiving embryos in year 1, it did not show significant impact in year 2 or following TAI in cattle consuming endophyte-infected tall fescue for both years.